Enriching Second-Screen Experiences with Automatic Content Recognition - Abreu, Jorge (2018)
Technological devices surrounding the television are changing, leading to changes in viewers’ habits and to the development of second-screen applications created to provide better TV viewing experiences. Used while watching television, the 2NDVISION application presented in this paper is able to identify – through audio-fingerprint – content being displayed on the TV screen and present enhanced information on the second screen. Under a participatory design approach, the development of the application took in consideration the users’ opinion regarding its main functionalities and interface solutions and included evaluation test sessions conducted in laboratory settings. This paper reports on the first evaluation sessions and the preliminary results gathered through a cognitive walk-through methodology, with opinions regarding instrumental, non-instrumental and emotional impact of the application collected through SUS, AttrakDiff and SAM scales. The results show that users experienced no major navigation problems and part of the iconography was validated. Considering the main goals of the application users were satisfied and interested in having such an application for providing additional information about the TV shows they watch.